Mekanisme Konstitusional Pemberhentian Hakim Konstitusi Dalam Sistem Ketatanegaraan Indonesia - Arian Bagas Prasetyo (Fakultas Syariah Univeritas Islam Madura, 2024)
This paper contains a supreme constitutional system that refers to several mechanisms for dismissing constitutional judges that raise several pros and cons to a case. Constitutional judges have very complex powers and duties, therefore a constitutional judge must be able to balance the independence as a judge, a position of judges who cannot be included in a branch of government that has the same position. And then the judge's decision must be final, not to be contested by other political interests. In the 1945 Constitution, several regulations have been listed governing the dismissal of Constitutional Judges, so any case regarding the dismissal of Constitutional Judges must be in accordance with existing regulations.